Cost Comparison Of Seismic Design For Reinforced Concrete Building Under Ranau Earthquake - Adha, Nor Amelia (Universiti Sains Malaysia, 2017)
Active plate boundaries can cause an earthquake to its nearest location including Malaysia. On 5th June 2015, an earthquake has occurred at Ranau, Sabah with magnitude of 6.0 Richter scale. Serious damages on certain building had occurred by the impact of this earthquake. Thus, structural engineers need solution to overcome this problem from happening again. The cost estimate for superstructure under seismic loading is important for engineers to analyze and have a better understanding on costing. Therefore, the cost estimation is important for Malaysia as preliminary information for construction player in preparation of the launch of Malaysia Annex to Standard Malaysia. This study focuses on comparison of cost between seismic and non-seismic design for three, six and nine storey with regular and irregular buildings. The analyses were carried out by using SAP 2000 software and calculated the beam and column design based on Eurocode 2. Results show that seismic design building has the higher cost in steel tonnage and concrete volume compared to the non-seismic design. The total cost of three storey under seismic design for regular building is 7.9 % higher compared to the non-seismic design building. The total cost of three storey under seismic design for irregular building is 21.9 % higher compared to the nonseismic design building. Next, the total cost of six storey under seismic design for regular building is 43.2 % higher compared to the non-seismic design building. The total cost of six storey under seismic design for irregular building is 46.9 % higher compared to the non-seismic design building. Besides that, the total cost of nine storey under seismic design for regular building is 13.1 % higher compared to the non-seismic design building. The total cost of nine storey under seismic design for irregular building is 43.2 % higher compared to the non-seismic design building.